Thymoquinone loading into hydroxyapatite/alginate scaffolds accelerated the osteogenic differentiation of the mesenchymal stem cells - Ebrahim Rahmani-Moghadam; Tahereh Talaei-Khozani; Vahideh Zarrin; Zahra Vojdani (BioMedical Engineering OnLine, 2021)
Abstract Background Phytochemical agents such as thymoquinone (TQ) have osteogenic property. This study aimed to investigate the synergic impact of TQ and hydroxyapatite on mesenchymal stem cell differentiation. Alginate was also used as drug vehicle. Methods HA scaffolds were fabricated by casting into polyurethane foam and sintering at 800 °C, and then, 1250 °C and impregnated by TQ containing alginate. The adipose-derived stem cells were aliquoted into 4 groups: control, osteogenic induced-, TQ and osteogenic induced- and TQ-treated cultures. Adipose derived-mesenchymal stem cells were mixed with alginate and loaded into the scaffolds Results The results showed that impregnation of HA scaffold with alginate decelerated the degradation rate and reinforced the mechanical strength. TQ loading in alginate/HA had no significant influence on physical and mechanical properties. Real-time RT-PCR showed significant elevation in collagen, osteopontin, and osteocalcin expression at early phase of differentiation. TQ also led to an increase in alkaline phosphatase activity. At long term, TQ administration had no impact on calcium deposition and proliferation rate as well as bone-marker expression. Conclusion TQ accelerates the differentiation of the stem cells into the osteoblasts, without changing the physical and mechanical properties of the scaffolds. TQ also showed a synergic influence on differentiation potential of mesenchymal stem cells.